Additional coronary sinus shocking lead as rescue therapy after multiple internal and external defibrillation failures. Issue 6 (26th April 2017) - Chauveau, Samuel; Dulac, Arnaud; Sebbag, Laurent; Morel, Elodie; Chevalier, Philippe
Key Clinical Message: High defibrillation threshold (DFT) and defibrillation failure can lead to intractable ventricular arrhythmias. Additional coronary sinus coil is an effective strategy to achieve marked reduction in DFT. However, physicians should retain this might prevent future coronary sinus lead placement in case the patient would develop complete left bundle branch block. Abstract : High defibrillation threshold (DFT) and defibrillation failure can lead to intractable ventricular arrhythmias. Additional coronary sinus coil is an effective strategy to achieve marked reduction in DFT. However, physicians should retain this might prevent future coronary sinus lead placement in case the patient would develop complete left bundle branch block.